Namibia - Whiting, Sharri (London : Kuperard ; New York : Distributed in the United States and Canada by Random House Distribution Services, 2008)
Culture Smart! provides essential information on attitudes, beliefs and behavior in different countries, ensuring that you arrive at your destination aware of basic manners, common courtesies, and sensitive issues. "Culture Smart! Namibia" provides essential information on attitudes, beliefs and behaviour in Namibia, ensuring that you arrive at your destination aware of basic manners, common courtesies, and sensitive issues. This concise guide will tell you what to expect, how to behave, and how to establish a rapport with your hosts. This inside knowledge will enable you to steer clear of embarrassing gaffes and mistakes, feel confident in unfamiliar situations, and develop trust, friendships, and successful business relationships.
Introduction --- Land and people -- Values and attitudes -- Beliefs, customs, and traditions -- Meeting Namibians -- The Namibians at home -- Time out -- Travel, health, and safety -- Business briefing -- Communicationg.
"The essential guide to customs & culture"--Cover.
Includes bibliographical references (page 165) and index.
Keywords: Namibia -- Social life and customs -- Handbooks, manuals, etc; Etiquette -- Namibia -- Handbooks, manuals, etc; National characteristics, Namibian; Namibia -- Guidebooks